Commodification and ‘the commons’: the politics of privatising public water in Greece and Portugal during the Eurozone Crisis - Bieler, Andreas; Jordan, Jamie (SAGE, 2017)
In response to the Eurozone crisis, austerity and restructuring has been imposed on the European Union’s (EU) peripheral member states in order to receive financial bailout loans. In addition to cuts in funding of essential public services, cuts in public sector employment and further liberalisation of labour markets, this has also included pressure towards the privatisation of state assets. And yet, workers have not simply accepted these restructuring pressures. They have organised and fought back against austerity and enforced privatisation. Based on a historical materialist perspective and following a strategy of incorporated comparison, in this paper we will comparatively assess the struggles against enforced water privatisation in Greece and Portugal set against the background of the structuring conditions surrounding the Eurozone crisis.